Regulation of hair cell and stomatal size by a hair cell-specific peroxidase in the grass Brachypodium distachyon - Nunes, Tiago D. G.; Berg, Lea S.; Slawinska, Magdalena W.; Zhang, Dan; Redt, Leonie; Sibout, Richard; Vogel, John P.; Laudencia-Chingcuanco, Debbie; Jesenofsky, Barbara; Lindner, Heike; Raissig, Michael Thomas (Current biology, 2023)
The leaf epidermis is the outermost cell layer forming the interface between plants and the atmosphere that must both provide a robust barrier against (a)biotic stressors and facilitate carbon dioxide uptake and leaf transpiration.1 To achieve these opposing requirements, the plant epidermis developed a wide range of specialized cell types such as stomata and hair cells. Although factors forming these individual cell types are known,2,3,4,5 it is poorly understood how their number and size are coordinated. Here, we identified a role for BdPRX76/BdPOX, a class III peroxidase, in regulating hair cell and stomatal size in the model grass Brachypodium distachyon. In bdpox mutants, prickle hair cells were smaller and stomata were longer. Because stomatal density remained unchanged, the negative correlation between stomatal size and density was disrupted in bdpox and resulted in higher stomatal conductance and lower intrinsic water-use efficiency. BdPOX was exclusively expressed in hair cells, suggesting that BdPOX cell-autonomously promotes hair cell size and indirectly restricts stomatal length. Cell-wall autofluorescence and lignin stainings indicated a role for BdPOX in the lignification or crosslinking of related phenolic compounds at the hair cell base. Ectopic expression of BdPOX in the stomatal lineage increased phenolic autofluorescence in guard cell (GC) walls and restricted stomatal elongation in bdpox. Together, we highlight a developmental interplay between hair cells and stomata that optimizes epidermal functionality. We propose that cell-type-specific changes disrupt this interplay and lead to compensatory developmental defects in other epidermal cell types.
Online verfügbar: 21. April 2023, Artikelversion: 8. Mai 2023
Gesehen am 26.07.2023